Intersecções entre moda e espetáculo: um estudo acerca do desfile de moda (ModaPalavra e-periódico, 2011)
This article proposes an analysis of the fashion show, in light of studies of the scene, looking for references in the fashion and spectacle theories. From literature review and observation of parades during the 18th edition of the Sao Paulo Fashion Week, held in January 2010, were elected the following for consideration of the fashion show as a spectacle: the performing space, sound, production of mannequins and moves on the catwalk. Assuming all that is exposed to the eye as spectacular, it was concluded that the fashion show is from the beginning a spectacle, and can therefore be appreciated as such.
Keywords: Fashion; Spectacle; Fashion show